INFLUENCE OF SAND DUNES ON THE ECOLOGICAL ENVIRONMENT - Abdunazarov Lutfillo Mamanovich; Meliqo’ziyeva Maxliyo Saydali's daughter; Murodova Odina Fayzullah’s daughter (Web of Journals Publishing, 2023)
Dunes, dynamic landforms created by wind and water, play a critical role in coastal ecosystems and desert regions. This article examines the environmental impacts of sand dunes, focusing on their ecological significance, conservation and management. Research examines how dunes mitigate coastal erosion, provide habitat for diverse flora and fauna, and influence local microclimates. It also explores human interactions with these ecosystems, looking at potential threats from tourism, urban development and climate change. By understanding the complex network of interactions in dune environments, we can better understand their ecological value and make informed conservation decisions.
Keywords: dunes, environmental impact, coastal ecosystems, desert regions, ecological significance, protection, management, coastal erosion, habitat, flora and fauna, microclimate, human interaction, tourism, urban planning, climate change, nature conservation.